Determining the role of FoF1-ATP synthase dimers in Trypanosoma brucei mitochondrial biogenesis - Hollaus, David (Jihočeská univerzita, 2020)
ATP synthase dimers have previously been identified to be major determinants of mitochondrial cristae ultrastructure. In order to determine the role of these dimers in the organellar architecture of Trypanosoma brucei, we performed a functional screen that identified a single T. brucei ATP synthase subunit that, upon depletion, destabilizes primarily dimers of the enzyme without disrupting the singular functional unit.
Determining the role of FoF1-ATP synthase dimers in Trypanosoma brucei mitochondrial biogenesis
Keywords: ATP synthase; Trypanosoma brucei; mitochondria; ATP synthase; Trypanosoma brucei; mitochondria